PENGARUH DISIPLIN KERJA, KOMUNIKASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI KANTOR SEKRETARIAT DPRD KABUPATEN KEPULAUAN MERANTI BAGIAN HUMAS DAN PROTOKOLER - A Gafur A Gafur; Indra Prasetyo; Woro Utari (BBM (Buletin Bisnis & Manajemen), 2022)
The purpose of this study was to analyze whether work discipline, communication and motivation affect the performance of the employees of the Secretariat Office of the Meranti Islands Regency Public Relations and Protocol Section. The population and sample in this study were all employees of the Secretariat Office of the Meranti Islands Regency DPRD, Public Relations and Protocol Section, totaling 37 people. The sampling technique in this research is total sampling. Multiple regression analysis was used for several independent influence variables on one dependent variable with a linear model. The results showed that work discipline, communication, motivation and performance of the employees of the Secretariat Office of the Meranti Islands Regency DPRD, Public Relations and Protocol Section, were all in good condition. Work discipline has a significant positive effect on performance, communication has a significant positive effect on performance and motivation has a significant positive effect on the performance of the employees of the DPRD Secretariat Office, Meranti Islands Regency, Public Relations and Protocol Section.